COMPLEX THERAPY OF PSICHOSOMATIC DISODERS IN PERIMENOPAUSAL PERIOD - Doubossarskaya, Yu.A.; Goncharenko, V.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
A therapy for psychosomatic disorders of perimenopausal  women with extragenital pathology, with use of Аdaptol which allows to decrease symptoms of climacteric disorders, depression and anxiety (which form psychosomatic climacteric disorders) and level of their mutual influense.